Medium-transferability and corpora: Remarks from the consumer-end of corpus linguistics - Esser, Jürgen (HERMES - Journal of Language and Communication in Business, 2017)
A distinction is made between units and categories that are medium-independent (e.g. word class, noun phrase and clause) and those that are tied to the medium of realization. While the orthographic sentence is a typical highly conventionalised unit that is tied to the written medium, the tone unit is a typical unit of the spoken medium. There are, however, some problems related to this unit of realisation. Not only is the tone unit and its organisation into higher-level units subject to theoretical dispute, it also has a different status in speaking and reading respectively, which so far has been largely ignored in corpus linguistics.